Risk Factors of Unsafe Behavior among Construction Workers - Sindy Septyana Putri; Anik Setyo Wahyuningsih (Universitas Diponegoro, 2024)
Globally, construction is considered the riskiest industry and construction workers have twice the risk of injury than workers in other jobs. PUPR Ministry data for 2017 states that construction is the largest contributor to accident cases in Indonesia with an average incidence of 32% each year. Unsafe behavior is the most common cause of work accidents. Based on observations, it was found that workers engaged in unsafe behavior in the Pekalongan City tidal food control project with an average incidence of 15% per day. This study aims to determine what factors are associated with unsafe behavior. The type of research used is analytic observational with a cross sectional approach and the sampling technique uses simple random sampling. The population of this study was 115 workers and the sample size was determine using the Slovin formula (error rate of 5%) obtained by 95 respondents. The research instruments used questionnairs and observation sheets. The results of the bivariate analysis showed that there was a significant connection between knowledge (p=0.006), supervision (p=0.000), and fatigue (0.000) on unsafe behavior. The results of the multivariate analysis show that supervision is the most powerful factor influencing unsafe behavior.